2004
DOI: 10.1124/mol.65.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation ofCYP2B1Induction in Primary Rat Hepatocyte Cultures: Repression by Epidermal Growth Factor Is Mediated via a Distal Enhancer Region

Abstract: Phenobarbital (PB) alters expression of numerous hepatic genes, including genes involved in xenobiotic metabolism. Phenobarbital-dependent induction of cytochrome P-450 2B1 (CYP2B1) is subject to regulation by cytokines [e.g., by epidermal growth factor (EGF)], hormones [e.g., by growth hormone (GH)], or the cellular redox status. To investigate mechanisms involved in regulation of CYP2B1 transcription, we performed promoter activation studies using primary rat hepatocyte cultures transiently transfected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…This finding explains why EGF repressed the CAR-mediated activation of CYP2B genes in rat primary hepatocytes (Bauer et al, 2004). It also agrees with the observation that U0126 augmented the induction of the CYP2B gene by PB in rat primary hepatocytes (Joannard et al, 2006).…”
Section: Erk-mediated Repression Of Car Translocationsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding explains why EGF repressed the CAR-mediated activation of CYP2B genes in rat primary hepatocytes (Bauer et al, 2004). It also agrees with the observation that U0126 augmented the induction of the CYP2B gene by PB in rat primary hepatocytes (Joannard et al, 2006).…”
Section: Erk-mediated Repression Of Car Translocationsupporting
confidence: 90%
“…These facts indicate that cellular signals are involved in regulating the cytoplasmic retention and nuclear translocation of CAR. Two observations providing insight into such a signal have been reported: the attenuation by epidermal growth factor (EGF) of CAR-mediated trans-activation of PBREM by PB and the augmentation by the MEK inhibitor U0126 of PB induction of the CYP2B gene in rat primary hepatocytes (Bauer et al, 2004;Joannard et al, 2006). MEK is a downstream protein kinase of EGF signaling and activates extracellular signal-regulated kinase (ERK).…”
mentioning
confidence: 99%
“…The involvement of the extracellular signal-regulated kinase (ERK) in the repression of CAR nuclear translocation is of particular interest. Previous work has shown that epidermal growth factor is able to attenuate CAR-mediated induction of CYP2B by PB treatment (Bauer et al, 2004). Inhibitors of mitogenactivated protein kinase kinase 1/2 (a kinase downstream of epidermal growth factor signaling) have been shown to potentiate the induction CYP2B by PB (Joannard et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…How is this dephosphorylation regulated? First, investigators found that growth factors such as EGF, hepatocyte growth factor, and insulin repress CAR activation and nuclear translocation in rat and/or mouse primary hepatocytes (Bauer et al, 2004;Koike et al, 2007;Yasujima et al, 2016). Therefore, CAR is, in principle, a cell signal-regulated nuclear receptor (Fig.…”
Section: Phenobarbital Induction Mechanismmentioning
confidence: 99%